Robotic assisted laparoscopic radical prostatectomy following transurethral resection of the prostate: perioperative, oncologic and functional outcomes - Chi-Feng Hung; Cheng-Kuang Yang; Yen-Chuan Ou (Prostate International, 2014)
The aim of this study was to assess surgical, oncologic and functional results after robotic-assisted laparoscopic radical prostatectomy (RALP) with and without previous transurethral resection of the prostate (TURP). Methods: Between December 2005 and January 2010, 200 patients underwent RALP, of whom 16 (8%) had received previous TURP and 184 (92%) had not. Perioperative and postoperative data were compared between those with previous TURP (group 1) and those without previous TURP (group 2). All patients included in the study had at least 1-year follow-up. Results: Preoperative clinical parameters were comparable between both groups. Group 1 patients were found to have significantly more need for bladder neck reconstruction (93.75 % vs. 15.21%, P<0.001), more rectal injury (18.75% vs. 0%, P<0.001), higher incidence of major complications (18.8% vs. 1.1%, P<0.001), and smaller specimen volume (31.63 mL vs. 45.49 mL, P<0.001) than group 2. The 12-month continence rate was 93.8 % in group 1 and 97.8% in group 2 (P=0.344). A nerve-sparing technique was significantly less successfully performed in group 1 patients than in group 2 (33.3% vs. 92.0 %, P=0.001). Conclusions: Performing RALP for prostate cancer in patients who have had previous TURP is a technically demanding procedure and may be potentially associated with a higher perioperative major complication rate in short-term follow-up. Neurovascular bundle preservation is technically more challenging.